48. THE DIETARY STATUS OF CHILDREN UNDER 24 MONTHS WITH PNEUMONIA TREATED INPATIENT AT THE NATIONAL CHILDREN'S HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2025)
Objective: To describe factors associated with malnutrition in children aged 6-60 months at the Pediatric Department, Quoc Oai district General Hospital in 2023.Method: A cross-sectional descriptive study was conducted on 341 children aged 6-60 months at the Pediatric Department, Quoc Oai district General Hospital, from March to September 2023. Data on nutritional status, feeding practices, 24-hour dietary intake, and medical history were collected and analyzed.Results: The prevalence of underweight, stunting, and wasting was 7.9%, 9.1%, and 9.1%, respectively. Factors associated with malnutrition included early weaning before 18 months (OR = 3.77, p < 0.05), lack of dietary diversity from 5/8 food groups (OR = 2.53, p < 0.05), recent illness within the past 3 months (p < 0.05), and household income below 3 million VND/month (p < 0.05).Conclusion: Malnutrition in children aged 6-60 months at Quoc Oai district General Hospital is closely linked to early weaning, inadequate dietary diversity, illness, and low household income. Strengthening nutritional education, promoting prolonged breastfeeding, and ensuring a diverse diet are essential to improve children’s nutritional status.
Keywords: Malnutrition; children; diet; weaning.